Pendidikan Akhlak di Sekolah: Perpaduan Keteladanan Guru dan Disiplin yang Konsisten - Didit Darmawan; Nur Nabila (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the internalization of akhlakul karimah through the combination of teacher personality competence and disciplinary consistency in shaping student morality. A qualitative library research design was employed, utilizing content analysis to synthesize conceptual and empirical literature. The findings reveal that teacher personality competence functions as a foundation providing living examples of how moral values are manifested in daily behavior. Teachers with mature personalities become identification figures inspiring students through exemplary conduct in patience, honesty, justice, and relational warmth. Disciplinary consistency provides a habituation framework enabling students to directly experience the consequences of each behavior through fair and consistent rule enforcement. The interaction between personal example and system consistency produces stronger internalization compared to when both factors work separately. This combination creates a moral education ecosystem where students not only understand values cognitively and habituate them behaviorally, but also appreciate them affectively through emotional bonds with teacher figures and experiences interacting with a fair system. Ultimately, what is formed is moral autonomy, the ability of students to behave well based on internal awareness, not because of external pressure. The study implies that teacher recruitment and development must proportionally attend to personality competence, schools need to build clear disciplinary systems implemented consistently by all parties, and integration between teacher personality development and disciplinary system strengthening is required within a unified policy framework.